Synthesis and properties of polyelectrolyte multilayered microcapsules reinforced smart coatings - Adnan Khan (696190) (2019)
The present research work focuses on the synthesis, characterization and properties of novel polyelectrolyte multilayered microcapsules used as smart additives in organic coatings for corrosion protection of steel parts. Urea formaldehyde microcapsules encapsulated with linalyl acetate (UFMCs), sensitive to mechanical stimulus, were synthesized by in situ emulsion polymerization technique. In the next step, dodecylamine, working as a pH stimulus corrosion inhibitor, was loaded into layers of polyelectrolyte molecules, polyethylenimine (PEI) and sulfonated polyether ether ketone (SPEEK). These were applied layer-by-layer over the microcapsules to form inhibitor containing multilayered urea formaldehyde microcapsules (MLUFMCs). In the next step, MLUFMCs (5.0 wt%) and UFMCs (5.0 wt%) were thoroughly dispersed into the epoxy resin and coated on cleaned steel. A comparison of the structural, thermal and anticorrosive properties indicates that coatings modified with multilayered capsules (PMLSCs) demonstrate good thermal stability, improved self-healing characteristics and higher corrosion resistance compared to the coating modified with urea formaldehyde microcapsules. The improved properties of PMLSCs can be attributed to efficient release of the encapsulated self-healing agent and corrosion inhibitor from the MLUFMCs. Therefore, epoxy coatings modified with the novel multilayered capsules may be attractive for corrosion protection of steel parts used in oil and gas and related industries. Other Information Published in: Journal of Materials Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10853-019-03761-9